The Mabo Turn in Australian Fiction - Rodoreda, Geoff; Rodoreda, Geoff (Peter Lang, 2018)
Winner of the Association for Anglophone Postcolonial Studies (GAPS) Dissertation Award 2018 This is the first in-depth, broad-based study of the impact of the Australian High Court's landmark Mabo decision of 1992 on Australian fiction. More than any other event in Australia's legal, political and cultural history, the Mabo judgement ? which recognised indigenous Australians' customary (S0(Bnative title(S1 (Bto land ? challenged previous ways of thinking about land and space, settlement and belonging, race and relationships, and nation and history, both historically and contemporaneously. While Mabo's impact on history, law, politics and film has been the focus of scholarly attention, the study of its influence on literature has been sporadic and largely limited to examinations of non-Aboriginal novels. Now, a quarter of a century after Mabo, this book takes a closer look at nineteen contemporary novels ? including works by David Malouf, Alex Miller, Kate Grenville, Thea Astley, Tim Winton, Michelle de Kretser, Richard Flanagan, Alexis Wright and Kim Scott ? in order to define and describe Australia's literary imaginary as it reflects and articulates post-Mabo discourse today. Indeed, literature's substantial engagement with Mabo's cultural legacy ? the acknowledgement of indigenous people's presence in the land, in history, and in public affairs, as opposed to their absence ? demands a re-writing of literary history to account for a ?Mabo turn? in Australian fiction.s